Analyzing the Allocation and Distribution of Irrigation Water Management Expenditures Among Different Regions in Uzbekistan - Rakhmonov Bekzod Sharibjon ugli (European Science Publishing, 2023)
This research paper aims to analyze the allocation and distribution of irrigation water management expenditures among different regions in Uzbekistan. The effective management of irrigation water resources is crucial for sustainable agricultural development and ensuring food security in the country. By examining the allocation patterns and distribution mechanisms of irrigation water management expenditures, this study seeks to shed light on the equity, efficiency, and effectiveness of resource allocation strategies across various regions. The research will employ a combination of quantitative analysis and qualitative assessment to identify disparities, challenges, and potential opportunities for optimizing the allocation of financial resources in Uzbekistan's irrigation sector. The findings of this study will provide valuable insights for policymakers, water managers, and stakeholders involved in irrigation water management decision-making processes.